2020
DOI: 10.1177/1420326x20980100
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prenatal and early-postnatal exposure to classical air pollution on childhood pneumonia in China

Abstract: To investigate the role of different pattern of ambient air pollutants exposure during early life on childhood pneumonia, we conducted a retrospective cohort study of 3226 preschool children aged three to six years in Shenzhen, China during 2015 to 2016. Each child's exposure to three main air pollutants (PM10, SO2 and NO2) was calculated by the inverse distance weighted method. Multiple logistic regression analysis was used to investigate the pneumonia risk of early life exposure to air pollution. A relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Level of education and household income were used as proxies for socioeconomic status (Madsen et al 2017 ; MacIntyre et al 2014 ; Shi et al 2021 ). Smoking status during pregnancy (active or passive) (Madsen et al 2017 ; MacIntyre et al 2014 ; Shi et al 2021 ; Liu et al 2022 ) and exposure to pesticides during pregnancy, as reported in the questionnaire, were considered potential confounders related to indoor environmental factors. Gestational age and birth weight were identified as potential confounders related to infant factors and were treated as numerical variables (Madsen et al 2017 ; MacIntyre et al 2014 ; Aguilera et al 2013 ; Liu et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Level of education and household income were used as proxies for socioeconomic status (Madsen et al 2017 ; MacIntyre et al 2014 ; Shi et al 2021 ). Smoking status during pregnancy (active or passive) (Madsen et al 2017 ; MacIntyre et al 2014 ; Shi et al 2021 ; Liu et al 2022 ) and exposure to pesticides during pregnancy, as reported in the questionnaire, were considered potential confounders related to indoor environmental factors. Gestational age and birth weight were identified as potential confounders related to infant factors and were treated as numerical variables (Madsen et al 2017 ; MacIntyre et al 2014 ; Aguilera et al 2013 ; Liu et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, postnatal exposure to PM 2.5 (Shi et al 2021 ) and NO 2 is linked to a higher risk of otitis media (Bowatte et al 2018 ; Shi et al 2021 ). A study in China revealed that PM 2.5 exposure was associated with a higher incidence of childhood pneumonia (Shi et al 2021 ), while another study showed that exposure to PM 10 and SO 2 during the first year of life was associated with an increased risk of pneumonia in children aged 3–6 years (Liu et al 2022 ). Similarly, a study in Brazil demonstrated that exposure to PM 10 and SO 2 in the first year of life is linked to an increased risk of pneumonia (Souza and Nascimento 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11] Exposure to air pollution, both indoors and outdoors, has been found to increase the risk of those diseases. [12][13][14][15][16][17][18] Early and lifetime exposures to dampness indicators is also linked to higher rates of respiratory and allergic diseases in children. [19][20][21][22] Similarly, the use of artificial synthetic materials in home decoration during pregnancy and early childhood has been associated with an increased risk of such diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers indicated that early-postnatal exposure to classical air pollution during the first year of children's life could have a key role in the development of childhood pneumonia. 28 Sun et al 29 found that PM 2.5 caused the highest DALYs lost (disability-adjusted life years) in office and school buildings, followed by formaldehyde, ammonia, benzene, toluene and xylene in a study of indoor air quality in the Yangtze River Delta region. DALYs 30 are a composite indicator used to compare the extent to which different diseases, injuries and risk factors could affect human health.…”
Section: Introductionmentioning
confidence: 99%